BAURAN PEMASARAN DIGITAL PRODUK MAKANAN DI RESTORAN PAN & CO - Widodo, Bambang; Oktarina, Shella (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2023)
In this era of digitalization, the development of food businesses in Indonesia has experienced a rapid increase, so companies have to implement various methods to market the products they sell. This research aims to determine and evaluate the marketing mix used at the Pan & Co Artisan Central Park Mall restaurant. This type of research is descriptive qualitative, data was obtained using the triangulation method through direct observation, interviews, and social media Instagram and TikTok. The data obtained was analyzed using 7P marketing mix analysis (Product, People, Price, Place, Process, Physical Evidence) with assessment scores using a Likert scale. The research results showed that the highest score for place was 5, followed by price and people 4.8, then physical evidence and product 4.6, then process 4.3 and finally the lowest was promotion, only 3.3. From the research results, it was concluded that the digital marketing mix using the 7P method was quite good, it just needed special emphasis on handling customer complaints and service standards, especially reviews on social media.